Alpha Oscillations and Early Stages of Visual Encoding - Klimesch, Wolfgang; Fellinger, Robert; Freunberger, Roman (Frontiers in Psychology, 2011)
For a long time alpha oscillations have been functionally linked to the processing of visual information. Here we propose an new theory about the functional meaning of alpha. The central idea is that synchronized alpha reflects a basic processing mode that controls access to information stored in a complex long-term memory system, which we term knowledge system (KS) in order to emphasize that it comprises not only declarative memories but any kind of knowledge comprising also procedural information. Based on this theoretical background, we assume that during early stages of perception, alpha ‘directs the flow of information’ to those neural structures which represent information that is relevant for encoding. The physiological function of alpha is interpreted in terms of inhibition. We assume that alpha enables access to stored information by inhibiting task irrelevant neuronal structures and by timing cortical activity in task relevant neuronal structures. We discuss a variety findings showing that evoked alpha and phase locking reflect successful encoding of global stimulus features in an early poststimulus interval of about 0 - 150 ms.